PENGARUH PENGANGGARAN BERBASIS KINERJA TERHADAP KINERJA KARYAWAN DI BLUD RSUD PALABUHANRATU KABUPATEN SUKABUMI - Abdul Haq (STISIP Widyapuri Mandiri Sukabumi, 2022)
Government financial management is one of the responsibilities of local governments or agencies in running the wheels of government. Nowadays, the process of preparing regional finances has shifted from the traditional budget concept to the new public management concept, which emphasizes performance rather than policies. Implementation of performance-based budgeting refers to the implementation of a budgeting system that is oriented towards organizational output in order to achieve performance goals and objectives. The performance budget approach focuses on organizational inputs, outputs, and outcomes, not solely on inputs. So this approach focuses on the management of efficient use of funds and the performance of employees and organizations. Thus, the benchmark for the success of this budget system is the performance or achievement of the objectives or results of the budget by using funds efficiently. The conclusions of the analysis in this study are: (1) performance-based budgeting in the BLUD RSUD Palabuhanratu is in the fairly good category, with a Descriptive Percentage (DP) value of 67.43% of the ideal value, (2) the performance of employees in the BLUD RSUD Palabuhanratu is included in the category good, with a Descriptive Percentage (DP) value of 73.25% of the ideal value, and (3) performance-based budgeting has a positive and significant effect on employee performance in the BLUD RSUD Palabuhanratu.